Prospective observational study to evaluate dermatology life quality index in patients with lichen sclerosus presenting to a tertiary care centre in Nepal - Shrestha, Elisha; Singh Basukala, Manisha; Mishra, Aditi; Shahi, Khushbu; Tamang, Ashish (Journal of Chitwan Medical College, 2025)
Introduction: Lichen sclerosus (LS) is a chronic inflammatory skin disease affecting the genital area, often leading to physical discomfort, anatomical changes, and reduced quality of life (QOL). The impact on QOL remains underexplored, particularly in resource-limited.Method: This prospective observational study on patients clinically diagnosed with LS who attended the dermatology outpatient department of Dhulikhel Hospital, Nepal, over six months from Jan to Jun 2024, after ethical approval. The QOL was assessed using validated Nepali version of Dermatology Life Quality Index (DLQI). Sociodemographic and clinical data were analysed for factors associated with higher impairment scores. A p-value